Embracing Cyberculture On Graphic Design - Romainoor, Nurul Hanim; Abdullah, Sarena (2016)
This paper is about exploring the concept of Cyberculture on graphic design. Today, people from the different background of age and culture are engaged in using personal computers, smartphones, and even digital cameras. They are known as the active media users. They are the new inventors of graphic design, digital images, animation and films in cyberspace. This study uses a thematic lens to describe writings on popular Cyberculture. The interesting part of this section is the construction of cyberpunk and cyborg that engaged in many popular Cyberculture writings. Two lenses derived from popular Cyberculture were assessed; one is cyberpunk and two is the cyborg. These two lenses are the foundation for reviewing Cyberculture on graphic design and a reflection of graphic design involvement with the computer and the Internet are discussed. The finding on graphic design in the lens of Cyberpunk seen in design illustration of favourite comic characters. Where, active media users may transform the iconic characters into cyberpunk that portray dark colours with streaks of neon colours and lighting.